2010
DOI: 10.1108/09578231011027833
|View full text |Cite
|
Sign up to set email alerts
|

School ethical climate and teachers' voluntary absence

Abstract: Purpose-This paper aims to offer a theoretical framework for linking school ethical climate with teachers' voluntary absence. The paper attempts to explain this relationship using the concept of affective organizational commitment. Design/methodology/approach-Participants were 1,016 school teachers from 35 high schools in Israel. Data were collected by self-report questionnaires and tested against archival data. The GENMOD procedure of SAS was applied. This procedure enables regression models for variables whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 62 publications
3
27
0
1
Order By: Relevance
“…Researchers have continued to examine the relationship between ethical climates and work attitudes including organizational commitment and job satisfaction. This work is generally supportive of the findings of the meta-analysis (Elçi & Alpkan, 2009;Filipova, 2009;Kim & Miller, 2008;Shafer, 2009;Shafer, Poon, & Tjosvold, 2013a;Shapira-Lishchinsky & Rosenblatt, 2010;Wang & Hsieh, 2012). For example, Filipova (2009) found that whilst caring climates were positively related to job satisfaction and organizational commitment, instrumental climates were negatively related to organizational commitment and positively related to turnover intentions.…”
Section: Work Attitudessupporting
confidence: 76%
“…Researchers have continued to examine the relationship between ethical climates and work attitudes including organizational commitment and job satisfaction. This work is generally supportive of the findings of the meta-analysis (Elçi & Alpkan, 2009;Filipova, 2009;Kim & Miller, 2008;Shafer, 2009;Shafer, Poon, & Tjosvold, 2013a;Shapira-Lishchinsky & Rosenblatt, 2010;Wang & Hsieh, 2012). For example, Filipova (2009) found that whilst caring climates were positively related to job satisfaction and organizational commitment, instrumental climates were negatively related to organizational commitment and positively related to turnover intentions.…”
Section: Work Attitudessupporting
confidence: 76%
“…Psychological withdrawal behaviors can be traced as willful lateness (Blau et al, 2004), intent to leave, and absenteeism (Koslowsky, 2009;Biron and Bamberger, 2012). Psychological withdrawal behavior describes the employees' behavior and attitudes responsible for the low level of job performance at the workplace (Johns, 1997;Shaw et al, 2005;Kaplan et al, 2009;Shapira-Lishchinsky and Rosenblatt, 2010). A low level of the social exchange relationship between leader and followers lowers down the employees' performance, commitment, and the job satisfaction level of the employees at the workplace (Rhoades and Eisenberger, 2002).…”
Section: Leader-member Exchange and Psychological Withdrawal Behaviormentioning
confidence: 99%
“…On one hand, an organization's members who perceive their organizational climate as ethical often show concern for the importance of corporate ethics and social responsibility (e.g. concern for stakeholders affected by their performance) [62]. On the other hand, employees who perceive an unethical organizational climate are likely to minimize the importance of ethics and social responsibility [63].…”
Section: Ethical Climatementioning
confidence: 99%